2019
DOI: 10.1002/14651858.cd011320.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Time-lapse systems for embryo incubation and assessment in assisted reproduction

Abstract: Analysis 2.1. Comparison 2 TLS utilising embryo selection so ware versus TLS with conventional morphological assessment of still TLS images (trial design 2), Outcome

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(52 citation statements)
references
References 53 publications
0
52
0
Order By: Relevance
“…Several studies investigated the clinical outcomes of medically assisted reproductive (MAR) cycles, comparing TLT to SIs. 4 A prospective randomized study analyzed blastocyst development and clinical outcomes of 64 single-embryo transfers performed in good prognosis patients to assess if the use of TLT compared to SI incubators can be advantageous in the clinical use. No statistical differences were found in terms of blastocyst quality, implantation, and pregnancy rates between the two groups.…”
Section: Time-lapse Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies investigated the clinical outcomes of medically assisted reproductive (MAR) cycles, comparing TLT to SIs. 4 A prospective randomized study analyzed blastocyst development and clinical outcomes of 64 single-embryo transfers performed in good prognosis patients to assess if the use of TLT compared to SI incubators can be advantageous in the clinical use. No statistical differences were found in terms of blastocyst quality, implantation, and pregnancy rates between the two groups.…”
Section: Time-lapse Systemmentioning
confidence: 99%
“…Despite the ever-growing interest in this field, the use of this technology to improve clinical outcomes remains controversial. 4 6 …”
Section: Introductionmentioning
confidence: 99%
“…To improve the efficacy and safety of ART, more precise approaches to embryo quality evaluation are needed, especially because a consensus was reached on single ET in ART cycles that elevated the urgency for accurate assessment of an embryo's implantation potential. Numerous studies reported the application of new tools in research, as well as in clinical practice, such as embryo biopsy and genetic diagnosis, 21 morphokinetic monitoring 22 and omics technology. 23 We believe searching for biomarkers in ECM is a more promising approach from a noninvasive and physiological perspective.…”
Section: Discussionmentioning
confidence: 99%
“…Undoubtedly, the advent of TLM has enabled collection of detailed images dynamically associated with a clinical endpoint. Albeit morphokinetics drive the way forward, further data may be required in supporting their beneficial role 62 leading to the conclusion that static observations may still have a lot to offer. It may be possible that an integration of both observation types, with clearer cut-off points and parameters, will improve clinical pregnancy and live birth rates.…”
Section: Future Research Recommendationsmentioning
confidence: 99%